Theoretical modelling of the translation process - Jeremiah Felix Nwachukwu (Cadernos de Tradução, 2024)
Translation Studies has undergone a significant transformation from a practice which relied on intuitive knowledge to a discipline with systematic approaches that have contributed in illuminating the intricate nature of translation. In the study of the translation process, for example, scholars and practitioners have introduced various models that explain the diverse dimensions of translation, covering cognitive, cultural, linguistic, sociological, and alternative perspectives. Although there has been an extensive exploration of the translation process through the cognitive lens, there is very little understanding of how it unfolds within other theoretical frameworks. This paper addresses this gap by introducing the concept of process modelling, illustrating how scholars from different theoretical backgrounds have dissected the translation process into distinct components. The objective is to emphasize that translation, as the process of “text production” in a different language, is a multifaceted operation involving several stages or phases. Through the lens of process modelling, the paper contributes to a deeper comprehension of the complexities inherent in translation.